Between capture and addition: The ontogenesis of cartographic calculation. (April 2020) - Hind, Sam
Abstract: This paper argues that cartographic calculation can be considered as a form of 'capture'. It suggests that surveillance narratives, typically used to illustrate sovereign forms of power, can be augmented by other socio-technical approaches. Accordingly, the paper develops the idea of capture from media studies to reframe cartographic calculation in computational terms. In doing so, it engages with work in political and digital geography, arguing that the rise of digital devices, apps, platforms and services have led to the generation of huge volumes of event-based knowledges; with significant implications for the study of the calculation. It subsequently argues that cartographic calculation is not, however, solely composed of calculative practices that simply capture cartographic data, but also necessarily composed of calculative practices that add knowledge into, and proliferate renders of, the world. Two dynamics of this oscillating process – anticipation and correspondence – expose the ontogenetic tendencies of cartographic calculation. The paper draws on the use of a digital protest mapping app to exemplify these forces.